Natural disturbances can produce misleading bioassessment results: Identifying metrics to detect anthropogenic impacts in intermittent rivers. Issue 2 (17th December 2019) - Soria, Maria; Gutiérrez‐Cánovas, Cayetano; Bonada, Núria; Acosta, Raúl; Rodríguez‐Lozano, Pablo; Fortuño, Pau; Burgazzi, Gemma; Vinyoles, Dolors; Gallart, Francesc; Latron, Jérôme; Llorens, Pilar; Prat, Narcís; et al.
Abstract: Ecosystems experience natural disturbances and anthropogenic impacts that affect biological communities and ecological processes. When natural disturbance modifies anthropogenic impacts, current widely used bioassessment metrics can prevent accurate assessment of biological quality. Our aim was to assess the ability of biomonitoring metrics to detect anthropogenic impacts at both perennial and intermittent sites, and in the latter including both flowing and disconnected pool aquatic phases. Specifically, aquatic macroinvertebrates from 20 rivers were sampled along gradients of natural flow intermittence (natural disturbance) and anthropogenic impacts to investigate their combined effects on widely used river biomonitoring metrics (i.e. taxonomic richness and standard biological indices) and novel functional metrics, including functional redundancy (i.e. the number of taxa contributing similarly to an ecosystem function, here a trophic function) and response diversity (i.e. how functionally similar taxa respond to natural disturbance and anthropogenic impacts). Only the widely used IBMWP index (Iberian Biological Monitoring Working Party) was able to detect anthropogenic impacts in intermittent rivers when used during flowing phases. Several functional metrics also detected anthropogenic impacts regardless of flow intermittence. Besides, functional redundancy of the entire community remained effective even in disconnected pools. Synthesis and applications . Our results show that natural flow intermittence can confound river bioassessment, and that a set of new functional metrics could be used as effective alternatives to standard metrics in naturally disturbed intermittent rivers. Our findings suggest that water managers should incorporate alternative functional metrics in the routine biomonitoring of naturally disturbed rivers. Abstract : Our results show that natural flow intermittence can confound river bioassessment, and that a set of new functional metrics could be used as effective alternatives to standard metrics in naturally disturbed intermittent rivers. Our findings suggest that water managers should incorporate alternative functional metrics in the routine biomonitoring of naturally disturbed rivers.